2010
DOI: 10.1161/circgenetics.109.861773
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Bilirubin and UGT1A1*28 Are Not Protective Factors Against First-Time Myocardial Infarction in a Prospective, Nested Case–Referent Setting

Abstract: Background-Bilirubin, an effective antioxidant, shows a large variation in levels between individuals and has been positively associated with reduced cardiovascular disease risk. A major reason for the variability is a common promoter polymorphism, UGT1A1*28, which reduces the transcription of the enzyme that conjugates bilirubin, UDPglucuronosyltransferase 1A1. The aim of the study was to evaluate a possible protective effect of plasma bilirubin and the UGT1A1*28 polymorphism against myocardial infarction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 45 publications
2
39
1
Order By: Relevance
“…Analysis according to sex Consistent with previous studies [4,5,19,27,28], our study showed that women had lower median bilirubin concentrations than men (8 vs 10 μmol/l). We found that the inverse relationship between bilirubin concentrations and risk of first amputation was highly significant for men (HR 1.60 per 5 μmol/l decrease in bilirubin concentration, 95% CI 1.19, 2.14, p=0.0017), but not women (HR 1.90 per 5 μmol/l decrease in bilirubin concentration, 95% CI 0.84, 4.33, p=0.126; p for interaction by sex= 0.71; Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Analysis according to sex Consistent with previous studies [4,5,19,27,28], our study showed that women had lower median bilirubin concentrations than men (8 vs 10 μmol/l). We found that the inverse relationship between bilirubin concentrations and risk of first amputation was highly significant for men (HR 1.60 per 5 μmol/l decrease in bilirubin concentration, 95% CI 1.19, 2.14, p=0.0017), but not women (HR 1.90 per 5 μmol/l decrease in bilirubin concentration, 95% CI 0.84, 4.33, p=0.126; p for interaction by sex= 0.71; Fig.…”
Section: Resultssupporting
confidence: 91%
“…This inverse association is further supported by studies showing a similar relationship between bilirubin levels and CHD, ischaemic stroke, and surrogate markers of atherosclerosis including endothelial dysfunction and carotid intima-media thickness [12,14,[29][30][31][32][33][34][35][36][37][38][39][40][41][42]. A number of prospective studies found a Uor reversed J-shaped relationship rather than an inverse relationship between bilirubin levels and CHD [4,5,27,28,30,33,34,37]. The differences between our study and these earlier studies are that they concentrated on CHD and mainly enrolled men, although whether these differences could plausibly explain the differing relationships reported is unclear.…”
Section: Discussionmentioning
confidence: 77%
“…The UGT1A1*28 genotype frequencies in our data correspond well with those expected for a white north European population. 15,26 Interpretation Our study diverges from previous studies by being population-based, by containing multiple causes of hyperbilirubinemia (eg, AB0 incompatibility, early discharge, starvation), by its case-control design, and by being to our knowledge the first to directly explore the association between UGT1A1*28 genotypes and extreme hyperbilirubinemia. Most studies find that the UGT1A1*28 allele is unrelated to neonatal hyperbilirubinemia, [27][28][29] but some studies have shown that UGT1A1*28 allele status is associated with increased levels of plasma bilirubin in conjunction with hemolytic factors (AB0 serum incompatibility, spherocytosis, and some variants of glucose-6-phosphate dehydrogenase deficiency).…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…For the AB0 incompatible subgroup, the number of cases, and thus statistic power, was more limited, which is reflected in wider confidence intervals. Because of the dose-response relationship between UGT1A1*28 genotypes and UGT1A1 enzyme activity, 15,16,26 in the primary analysis the genotypes were treated as a continuous variable and as a categorical variable in the secondary analysis. Effect estimates were similar for the 2 analytic strategies, but the primary analysis had a higher statistical power and a better precision of estimates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation